Ženske persone u kontekstu Danove erotologije (Philologia, 2021)
The paper examines four female persona poems by john Donne with a view to ascertaining the degree in which they conform to or differ from the patterns of Donne’s erotology as established within the larger body of his (male persona) poetry. The analysis shows that erotological implications of these poems are mainly slightly modified attitudes of Donne’s male persona poems, or extreme and half serious alternatives to the erotological positions of the male persona poems. Hence, their importance is by no means ground breaking inasmuch as they do not offer enough to justify a full-scale refocusing of Donne’s erotology; their significance rather lies in the fact that they do add some special colour and variety to Donne’s heterogeneous approach to the theme of love.
Keywords: female; subject/persona; love; eros; erotology